The impact of FinTech start-ups on incumbent retail banks' share prices - Yinqiao Li; Renée Spigt; Laurens Swinkels (Financial Innovation, 2017)
Background: This study aims to clarify the role of FinTech digital banking start-ups in the financial industry. We examine the impact of the funding of such start-ups on the stock returns of 47 incumbent US retail banks for 2010 to 2016. Methods: To capture the importance of FinTech start-ups, we use data on both the dollar-volume of funding and number of deals. We relate these to the stock returns with panel data regression methods. Results: Our results indicate a positive relationship exists between the growth in FinTech funding or deals and the contemporaneous stock returns of incumbent retail banks. Conclusions: Although these results suggest complementarity between FinTech and traditional banking, we note that our results at the banking industry level are not statistically significant, and that the coefficient signs for about one-third of the banks are negative, but not statistically significant. Since the FinTech industry is young and our sample period short, we cannot rule out that our findings are spurious.
Keywords: 650; Banks; Digital banking; Finance; FinTech; Innovation; Retail banks; Start-ups; Stock returns; Venture capital; Technology